The Escherichia coli alkA Gene Is Activated to Alleviate Mutagenesis by an Oxidized Deoxynucleoside - Grøsvik, Kristin; Tesfahun, Almaz Nigatu; Muruzábal-Lecumberri, Izaskun; Haugland, Gyri Teien; Leiros, Ingar; Ruoff, Peter; Kvaløy, Jan Terje; Knævelsrud, Ingeborg; Ånensen, Hilde; Alexeeva, Marina; Sato, Kousuke; Matsuda, Akira; et al. (Frontiers in Microbiology, 2020)
The cellular methyl donor S-adenosylmethionine and other endo/exogenous agents methylate DNA bases non-enzymatically into products interfering with replication and transcription. An important product is 3-methyladenine (m3A), which in Escherichia coli is removed by m3A-DNA glycosylase I (Tag) and II (AlkA). The tag gene is constitutively expressed, while alkA is induced by sub-lethal concentrations of methylating agents. We previously found that AlkA exhibits activity for the reactive oxygen-induced thymine (T) lesion 5-formyluracil (fU) in vitro. Here, we provide evidence for AlkA involvement in the repair of oxidised bases by showing that the adenine (A) · T to guanine (G) · cytosine (C) mutation rate increased ten-fold in E. coli wild-type and alkA− cells exposed to 0.1 mM 5-formyl-2´-deoxyuridine (fdU). The wild-type specific reduction of the mutation rate at 0.2 mM fdU correlated with alkA gene induction. G·C to A·T alleviation occurred without alkA induction (at 0.1 mM fdU), correlating with a much higher AlkA efficiency for fU opposite to G than for that to A. The common keto form of fU is the AlkA substrate. Mispairing with G by ionised fU is favoured by its exclusion from the AlkA active site.